UNDERSTANDING AND IMPROVING THE PREVENTION OF PEOPLE TRAFFICKING THROUGH OBSERVATION AT CLASS I IMMIGRATION OFFICE NON TPI BEKASI - Trisapto Wahyudi Agung Nugroho; W Wilonotomo (Polteknik Imigrasi, 2023)
Trafficking in persons is a serious threat to human rights that requires effective preventive measures. This study applies the observation method to explore efforts to prevent trafficking in persons at the Immigration Office Class I Non TPI Bekasi. Observations were made to reveal prevention practices in real contexts, interactions between officers and the public, as well as the impact of prevention programs. The observation results indicate that the Immigration Office has adopted various strategies to prevent trafficking in persons. Through the document inspection process, officers carefully identify potential falsification of identity and travel documentation. Outreach programs play an important role in increasing the awareness and understanding of the public and officials about trafficking in persons. The interaction between officers and the community seems to be going well, with the community responding positively to prevention efforts. Observations also reveal that cooperation with external agencies, such as the police and non-governmental organizations, plays a role in sharing information and handling cases. However, the observations also identified challenges, such as the existence of complex situations and the dynamics of cross-border corridors. Observations indicate that policy adaptation and improvement of prevention practices can contribute to overcoming this challenge. Taking into account the results of observations, this study provides an in-depth understanding of the prevention of trafficking in persons at the Immigration Office Class I Non TPI Bekasi. The practical implications of this research involve improving prevention processes, increasing the effectiveness of outreach programs, and developing cross-sectoral collaboration. As such, observation emerges as an important method of understanding and strengthening efforts to prevent trafficking in persons in this environment.